2020
DOI: 10.1111/1744-7917.12774
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 10 controls chitin amounts and organization in the wing cuticle of Drosophila

Abstract: Wings are essential for insect fitness. A number of proteins and enzymes have been identified to be involved in wing terminal differentiation, which is characterized by the formation of the wing cuticle. Here, we addressed the question whether chitinase 10 (Cht10) may play an important role in chitin organization in the wings of the fruit fly Drosophila melanogaster. Initially, we first found that Cht10 expression coincides with the expression of the chitin synthase coding gene kkv. This suggests that the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…In a recent study, Dong et al . (2020) showed that Cht10 is involved in regulating the morphology and function of the D . melanogaster wing cuticle, which in turn affects its flying ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Dong et al . (2020) showed that Cht10 is involved in regulating the morphology and function of the D . melanogaster wing cuticle, which in turn affects its flying ability.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SfCht10 silencing also induced phenotypic defects and high mortality during nymph-adult transition of S. furcifera, which indicates that SfCht10 is essential for nymph-adult transition of S. furcifera. In a recent study, Dong et al (2020) showed that Cht10 is involved in regulating the morphol-ogy and function of the D. melanogaster wing cuticle, which in turn affects its flying ability. In S. furcifera, we found that, when SfCht10 was suppressed by RNAi, the lethal rate at 96 h was 77% in the nymph stage and the surviving 23% of insects could normally emerge as adults with no visible wing malformation; this indicates that SfCht10 is a lethal gene.…”
Section: Discussionmentioning
confidence: 99%
“…The group II chitinase (ChtII, also known as Cht10) is a very large chitinase containing 4–5 catalytic domains (CADs) and 4–7 chitin‐binding domains (CBDs). The function of this gene has been studied in many insect species (Royer et al ., 2002; Zhu et al ., 2004; Zhu et al ., 2008a; Nakabachi et al ., 2010; Zhang et al ., 2011b; Pan et al ., 2012; Tetreau et al ., 2015; Liao et al ., 2016; Dong et al ., 2020). It was mainly expressed in the integument during molting and was essential for molting in L. migratoria (Li et al ., 2015), N. lugens (Xi et al ., 2015), Chilo suppressalis (Su et al ., 2016) and O. furnacalis (He et al ., 2013) as assessed by RNAi.…”
Section: Introductionmentioning
confidence: 99%
“…An insect's cuticle has multiple functions, such as shaping the inner organs and protecting against dehydration and penetration by xenobiotics and pathogens (Dong et al ., 2020). A main component of the cuticle is polysaccharide chitin, which interacts with chitin‐binding proteins (Moussian et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%